Factors Associated with Opisthorchiasis in Nong Pling Subdistrict, Mahasarakahm province, Thailand - Sirithanawutichai, Teabpaluck; Thongkajai, Pramote; Wongsawad, Chalobol; Kampangsri, Wilas; Promsuan, Pacharamon; Nithikathkul, Choosak (Journal of Health Science of Thailand, 2017)
The common practice of consumption of uncooked or freshwater fish has been found to be associated with fish-borne parasitic infestation which remains to be a major public health problem, particularly in the North-eastern region of Thailand. Previous reports indicated that metacercaria of some fish-borne parasites with the potential to cause diseases were found in freshwater fish. The objective of this study was to determine the incidence of intestinal and fish-borne parasitic infestation during a period of low infection among the residents of Nong Pling sub-district, Muang, Mahasarakham province, Thailand. Stool survey was conducted during the year 2014 among villagers in communities 5 and 6 in Nong Pling sub-district, Muang district, Mahasarakham province, using formalin ether concentration techniques. There were 141 stool samples collected from 63 male and 78 female villagers with average age of 46.45 years old. As for the results, there were 20 villagers with helminthaisis, giving the prevalence of 14.2%; including 8 cases of Strongyroides stercoralis (5.7%), 4 cases of Opisthorchis viverrini (2.8%), and 4 cases of Taenia spp. (2.8%). The highest (21.1%) and lowest (0.00%) rates of infestation were observed in age groups of 40-49 and 5-29 years old, respectively. Based on the result of this study, it was concluded that mass treatment for Opisthorchiasis and helminthiasis in the Thai population targeting high risk individuals might be cost-effective way to utilize the limited funds. The authors recommended that further study should be conducted on the correlation between the symptoms and the parasitic infestation in order to obtain useful data for the development of comprehensive strategy on helminthiasis.